Randomized, Open-Label, Phase 1/2a Study to Determine the Maximum Tolerated Dose of Intraventricular Sustained Release Nimodipine for Subarachnoid Hemorrhage (NEWTON [Nimodipine Microparticles to Enhance Recovery While Reducing Toxicity After Subarachnoid Hemorrhage]). Issue 1 (January 2017) - Hänggi, Daniel; Etminan, Nima; Aldrich, Francois; Steiger, Hans Jakob; Mayer, Stephan A.; Diringer, Michael N.; Hoh, Brian L.; Mocco, J; Faleck, Herbert J.; Macdonald, R. Loch
Abstract : Background and Purpose—: We conducted a randomized, open-label, phase 1/2a, dose-escalation study of intraventricular sustained-release nimodipine (EG-1962) to determine safety, tolerability, pharmacokinetics, and clinical effects in aneurysmal subarachnoid hemorrhage. Methods—: Subjects with aneurysmal subarachnoid hemorrhage repaired by clipping or coiling were randomized to EG-1962 or enteral nimodipine. Subjects were World Federation of Neurological Surgeons grade 2 to 4 and had an external ventricular drain. Cohorts of 12 subjects received 100 to 1200 mg EG-1962 (9 per cohort) or enteral nimodipine (3 per cohort). The primary objective was to determine the maximum tolerated dose. Results—: Fifty-four subjects in North America were randomized to EG-1962, and 18 subjects were randomized to enteral nimodipine. The maximum tolerated dose was 800 mg. One serious adverse event related to EG-1962 (400 mg) and 2 EG-1962 dose-limiting toxicities were without clinical sequelae. There was no EG-1962-related hypotension compared with 17% (3/18) with enteral nimodipine. Favorable outcome at 90 days on the extended Glasgow outcome scale occurred in 27/45 (60%, 95% confidence interval 46%–74%) EG-1962 subjects (5/9 with 100, 6/9 with 200, 7/9 with 400, 4/9 with 600, and 5/9 with 800 mg) and 5/18 (28%, 95% confidence interval 7%–48%, relative risk reduction of unfavorable outcome; 1.45, 95% confidence interval 1.04–2.03; P =0.027) enteral nimodipine subjects. EG-1962 reduced delayed cerebral ischemia (14/45 [31%] EG-1962 versus 11/18 [61%] enteral nimodipine) and rescue therapy (11/45 [24%] versus 10/18 [56%]). Conclusions—: EG-1962 was safe and tolerable to 800 mg, and in this, aneurysmal subarachnoid hemorrhage population was associated with reduced delayed cerebral ischemia and rescue therapy. Overall, the rate of favorable clinical outcome was greater in the EG-1962-treated group. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01893190. Abstract : Supplemental Digital Content is available in the text.